2022
DOI: 10.3389/fcimb.2022.1006576
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pelvic floor electrical stimulation on vaginal microbiota and immunity

Abstract: Pelvic floor electrical stimulation (ES) is an effective treatment for pelvic floor dysfunction. However, the impact of ES on vaginal microbiota and local inflammatory response is yet poorly understood. Therefore, we designed a longitudinal study to investigate the impact of ES on vaginal microbiota and cytokines. A total of 170 participants were recruited into the study at Peking University International Hospital, Beijing, China, from December 2021 to April 2022. They were divided into two groups concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…From the 4th session, the biofeedback therapy was added into the therapeutic regimen. For each patient, ES treatments were conducted for 15 min, followed by 15 min of Kegel exercise with the assistance of biofeedback [ 5 ]. The instruments used in ES treatments were Vishee biostimulation feedback instrument (MLD B4, Nanjing Vishee Medical Technology Co., Ltd., Nanjing, China) and surface electromyography (EMG) electrode (Nanjing Vishee Medical Technology Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 4th session, the biofeedback therapy was added into the therapeutic regimen. For each patient, ES treatments were conducted for 15 min, followed by 15 min of Kegel exercise with the assistance of biofeedback [ 5 ]. The instruments used in ES treatments were Vishee biostimulation feedback instrument (MLD B4, Nanjing Vishee Medical Technology Co., Ltd., Nanjing, China) and surface electromyography (EMG) electrode (Nanjing Vishee Medical Technology Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…Electrical stimulation (ES), which can excite nerves and stimulate pelvic floor muscles (PFMs) by sending mild electrical currents, is an effective method to increase voluntary pelvic muscle contractions and enhance muscle strength [ 5 ]. It has been reported that the even muscles suffering from severe impairment can be benefited from ES to perform voluntary contractions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%